Solid Organ Transplantation and Body Contouring Surgery: A Case Series and Single-Center Experience - Philipp Tratnig-Frankl; Andrea Wiland; Christian Freystätter; Eva Placheta-Györi; Christine Radtke (Journal of Clinical Medicine, 2026)
Background: In recent years, the number of patients seeking body contouring surgeries after a single organ transplantation has increased due to better postoperative care, better immunosuppressive regimens and the advancement of laparoscopic bariatric surgical techniques. In these patients, body contouring procedures can improve function, aesthetics, and overall quality of life and are offered to a greater number of patients including cohorts with significant medical comorbidities such as immunosuppression after solid organ transplantation. Therefore, in this case series, we explored the topic of body contouring surgery in patients who underwent solid organ transplantation. Methods: In this retrospective study, we included patients who underwent a single organ transplantation prior to a body contouring surgery between 2010 and 2021. Inclusion criteria were age over 18 years, a body contouring surgery at our center, a single organ transplantation before the body contouring procedure and a postoperative follow up of four weeks or more. Results: A total of 422 patients underwent body contouring procedures in our center. After excluding non-eligible patients, four patients were recruited. Overall, four complications in three patients occurred, ranging from Grade I to II according to the Dindo and Clavien classification for surgical complications. Conclusions: Body contouring surgery seems to be safe in patients with single organ transplantation. However, careful patient selection in a multidisciplinary team is required to ensure patients’ safety and favorable postoperative outcomes in patients with extended operative indications and significant comorbidities such as solid organ transplantation and immunosuppression. Complex patients should be treated in close collaboration with transplant surgery and internal medicine at a tertiary center.